Hubungan Metode Bercerita dengan Karakter Siswa Di Madrasah Ibtidaiyah Negeri 1 Purbalingga - Siti Mangunah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
This research is based on the importance of character in creating a young generation with good character. In this regard, this study aims to determine the relationship between the storytelling method and the character of students at MIN 1 Purbalingga. This study uses a quantitative research approach. While the type of research used in this research is a quasi-experimental design or quasi-experimental design. The experimental design used in this study was a "pretest-posttest control group design" or a pretest and posttest group design involving two groups. The learning category is divided into two categories, namely the experimental class doing storytelling activities. While the control class did not do storytelling activities. Data collection uses a questionnaire or questionnaire, also supported by interview techniques, observation, and documentation. The method of data analysis in this study is using: (1) Descriptive Statistics; (2) Test of Equality of Error Variances; and (3) Test of Between-Subjects Effects. This research concludes that: The significance of the Storytelling Method is 0.000. Because of the significance <0.05 (0.000 <0.05), then Ho is rejected. So, it can be concluded that there is a difference in the average value of student character between learning using the storytelling method and learning that does not use the storytelling method.